1517The effect of pregnancy on cardiovascular health in early adulthood: a difference in difference analysis. (2nd September 2021) - Clayton, Gemma; Howe, Laura; Parks, Chloe; Leyland, Kirsten; Hughes, Alun; Fraser, Abigail
Abstract: Background: Pregnancy causes extreme cardiometabolic changes, yet evidence of its long-term cardiovascular effects is limited. Our aim was to estimate the causal effect of pregnancy on cardiovascular health. Methods: We used a difference-in-difference (DiD) model to estimate the causal effect of pregnancy on multiple cardiovascular health measures (N = 445–1822 for cardiac echocardiography, blood based markers, blood pressure (BP) and anthropometry) in female participants in the Avon Longitudinal Study of Parents and Children with a pregnancy between 18-25 years. We differentiated between live birth and miscarriage/termination. Briefly, DiD assumes baseline differences in the outcome reflect confounding, that the rate of change in the outcome is similar in exposed and unexposed prior to the exposure, and that no new confounding was introduced after baseline. Any DiD at follow up is then attributed to the exposure. Results: 289 women had a pregnancy between ages 18-25 (15%). We found no effect of pregnancy on various echocardiography measures including left ventricular mass index. When accounting for changes in BMI, HDL-c and systolic BP at age 25 was -0.22mmol/L (95%CI:-0.28, -0.15) and -1.37mmHg (95%CI:-3.25, 0.52) lower, respectively, in women who had a live birth compared to no pregnancy. BMI, fat mass, and lean mass were higher in women who had a live birth versus no pregnancy. Conclusions: Findings are consistent with limited existing evidence of BP lowering and lipid increasing effects of pregnancy. Future studies should investigate underlying mechanisms. Key messages: Pregnancy results in a reduction in systolic BP and an adverse effect on HDL-c levels.